Analysis of Non-Revenue Water reduction using the FAVAD method in DMA planning: Case study in Palangka Raya drinking water supply system - Fahreza Alvian Nanda; Ali Masduqi; Agus Ahyar; Ade Syaiful Rachman (Center for Science and Technology, IAIN Surakarta, 2023)
Non-revenue water (NRW) is a crucial problem for the Perusahaan Umum Daerah Air Minum (PERUMDAM) Palangka Raya due to its extensive service area, lacking metered divisions that hinder leak detection in the distribution pipe network. This research explores the potential for reducing NRW levels by establishing a district meter area (DMA) within the central drinking water supply system (SPAM) PERUMDAM Palangka Raya service area. DMA configuration, designed to meet specific distribution pipe criteria, is carried out through the EPANET 2.2 program. This study aims to identify the decrease in NRW through the implementation of the Fix and Variable Area Demand (FAVAD) pressure management method. Due to limited resources, a priority assessment for DMA formation was performed using the Weight Sum Model (WSM) method. The analysis results show the possibility of dividing the central drinking water supply system service area into 27 DMAs, with the formation of DMA I/11 identifies as the highest priority DMA. After the DMA was established, the NRW component that decreased was water loss caused by pipe leaks, resulting in a saved amount of 15,261 m3/month. This reduction contribute to a dicrease in NRW levels by 6.06%, preventing clean water scarcity in Palangka Raya City.